1990
DOI: 10.1007/bf00049305
|View full text |Cite
|
Sign up to set email alerts
|

Parametric stochastic convexity and concavity of stochastic processes

Abstract: Sample path convexity and concavity, Markov processes, directional convexity and concavity, single stage queues, supermodular and submodular functions, L-superadditive functions, reliability theory, branching processes, shock models, total positivity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 15 publications
1
77
0
Order By: Relevance
“…They triggered the interest in comparison of queues with similar inputs ( [6,22,28]). The notion of a dcx function was partially developed and used in conjunction with the proving of Ross-type conjectures ( [19,20,31]). Much earlier to these works, a comparative study of queues motivated by neuronfiring models can be found in [14].…”
Section: Introductionmentioning
confidence: 99%
“…They triggered the interest in comparison of queues with similar inputs ( [6,22,28]). The notion of a dcx function was partially developed and used in conjunction with the proving of Ross-type conjectures ( [19,20,31]). Much earlier to these works, a comparative study of queues motivated by neuronfiring models can be found in [14].…”
Section: Introductionmentioning
confidence: 99%
“…We recall this concept, introduced in Shaked and Shanthikumar (1990), also studied by Meester and Shanthikumar (1993;1999) and Chang et al (1994). Recent applications can be seen in Escudero and Ortega (2008) and Fern谩ndez-Ponce et al (2008).…”
Section: Mathematical Backgroundmentioning
confidence: 97%
“…This fact allows us to obtain good results for geometric random sums. We observe that the stochastic directional convexity was introduced by Shaked and Shanthikumar (1990), when parameters take values in convex subsets of the real line. These structural properties, intuitively, describe how some random objects grow convexly (or concavely) with respect to their parameters.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observe that the variability of the reinsured total claim amount under stop-loss reinsurance is a more general issue than the study of the stop-loss premiums. We also obtain stochastic directional convexity properties (see Shanthikumar 1990 andShanthikumar 1999) for the families of parameterized random variables describing the retained and the reinsured total claim amounts. First applications of stochastic directional convexity can be found in operational research problems, mainly on queueing systems.…”
Section: Introductionmentioning
confidence: 99%